Web-Based MSMEs Promotion Catalog System Design in Pekan Kuala Using Agile Scrum - Perwitasari, Ika Devi; Jodi Hendrawan; Sitepu, Fernando; Wildanur Anggraini (Journal of Informatics Management and Information Technology, 2024)
This study aims to design and develop a web-based promotion catalog system to support the micro, small, and medium enterprises (MSMEs) in Pekan Kuala. With increasing competition in the marketplace, the MSMEs sector needs an effective platform to promote products and services to a wider audience. The proposed system is built using a web-based framework, offering an accessible and user-friendly interface that enables MSMEs to manage and showcase their products online. To ensure an efficient development process, this project adopts the Agile Scrum methodology, which emphasizes iterative progress, adaptability, and close collaboration between stakeholders. The system was developed in phases, including requirements gathering, design, implementation, and testing. Agile Scrum allowed for continuous feedback and improvements, resulting in a flexible and scalable solution. The final product not only streamlines the promotion process for MSMEs but also enhances their online visibility, potentially boosting sales and market reach. The system’s usability and effectiveness were evaluated through user testing, with positive feedback from both MSMEs participants and potential customers. This research highlights the benefits of Agile Scrum in developing tailored digital solutions for local businesses and underscores the potential of web-based systems in empowering small enterprises.